Adolescent fast food consumption: implications for healthful living (2012)
The development of quality of life requires conscious ana positive attitude towards safe living, healthy consumption and the understanding of individual responsibility in consumer health. Available evidences clearly suggest that adequate and quality nutrition is very necessary for adolescents to live a healthy life. The implication of fast food consumption on adolescents’ health is analyzed in this work thus; dietary need of adolescents, why adolescent's prefer fast food and finally the implications of eating fast foods. The authors believed that adolescents should consider living a healthy life and not one detrimental to their health due to wrong dietary habit. Adolescents should therefore be sensitized and encouraged through health education to make the right dietary choices.